3(-1)-2y=32

Simple and best practice solution for 3(-1)-2y=32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-1)-2y=32 equation:



3(-1)-2y=32
We move all terms to the left:
3(-1)-2y-(32)=0
determiningTheFunctionDomain -2y-32+3(-1)=0
We add all the numbers together, and all the variables
-2y-35=0
We move all terms containing y to the left, all other terms to the right
-2y=35
y=35/-2
y=-17+1/2

See similar equations:

| 14(4r-8)=r-2 | | -7c+6=-8c | | -9+w/3=-4 | | -5f=-45= | | 9/7-5/2u=-4/3 | | -4=-11+b/3 | | -4g^2+6=-10 | | 13t-7=36 | | 3p=8+2p | | y-2(3y+1)=4(y-1) | | .75=3p+5.88 | | 8m+m=9 | | 3/4n=9/6 | | -2y+3+7y=-12 | | 4u+9u=0 | | 4(v-3))-6v=-2(v+6) | | 6r=-9+5r | | 1/4y-6=-10 | | 8-7c=36 | | 7x+10+10x-14=13 | | d-2=-7= | | 8–7c=36 | | -3z-8z=33 | | 11x-3x+84=11x+48 | | 6(4-2y)+5(3y+1)=41 | | 7x+5(-2x-3)=-3 | | 1/4m^2+2m-5=0 | | -3z–8z=33 | | 6(2x-4)+2x=46 | | 10x-6x+193=10x+108 | | 30=-5(1+t) | | 1/4m^2-5=0 |

Equations solver categories